Caracterizacão geofísica de mineralizacões de cobre na porção leste de Canaã dos Carajás, província mineral de Carajás - Pinheiro, Josefa Deidyane Alves (2024)
The growing demand for energy transition metals, combined with the abundance and diversity of mineral resources on Brazil in the recent years has made the mining industry responsible for a large part of the country's economy. Copper (Cu), one of the raw materials widely used in various technologies related to carbon-free economies, is the second most exported metallic substance from Brazil. However, Cu reserves have been decreasing worldwide, making it necessary to discover and explore new deposits or reevaluate existing ones. With this in mind, this study aims to identify, through the geophysical characterization and drill hole data, an area favorable for the presence of a new Cu deposit, in addition to seeing the possible similarity of this deposit to the Iron Oxide-Copper-Gold (IOCG) deposits. The study area is located in the municipality of Canaã dos Carajás, State of Pará. Within the Carajás Domain, the region is characterized by rocks of the Xingu Complex, characterized by locally hydrothermalized granodiorites, granites, gabbros, metabasalts and metarhyolites. This area is located in the Carajás Mineral Province (PMC), which hosts numerous world-class, high-grade IOCG-type deposits. Data from 15 electrical resistivity and induced polarization (IP) sections acquired by electrical tomography techniques using dipole-dipole and pole-dipole arrays with 10-meter electrode spacing were used. In addition to the geophysical data, 31 drill holes and detailed geological mapping were used. These were employed for 2D inversion of the profiles and 3D modeling of the geophysical and geological data. The inverted sections showed large variations in resistivity values (minimums close to 6 Ohm.m and maximums over 55,000 Ohm.m) and chargeability (ranging from approximately 0 to 320 msec). Some conductive regions associated with polarizable anomalies correspond to sulfide zones, however, sulfide mineralization can also be correlated to intermediate to high resistivity values, which can be seen in the 3D models. As for chargeability, values above 20 msec are predominant and are associated with the sulfide zone. The 3D geological model allowed us to see the alignment of some lithologies with local and regional faults and fractures in a NE-SW direction. Furthermore, according to the geology of the area, although mineral paragenesis, stratigraphic conditioning, hydrothermal alterations and disseminated sulfides are considered common characteristics in IOCG-type deposits, more detailed studies are recommended to confirm or not this correlation. In any case, this study concluded that the methodology used (electro-resistivity and induced polarization) can improve exploration and resource estimation strategies in similar geological scenarios.